Jung and Phenomenology: Chiasm and Communion. (3rd April 2017) - Guthrie, Leland
Abstract : Western culture suffers from an illusion of separation between the mental and the physical, which is mirrored in the rift between psyche and the Earth. Jungian phenomenology offers a way to heal this rift by returning to direct experiential encounters with the beings and presences of the physical and imaginal worlds.